2019
DOI: 10.3389/fenrg.2019.00062
|View full text |Cite
|
Sign up to set email alerts
|

Blue Energy Potential Analysis in the Mediterranean

Abstract: This paper describes the status of the potential of blue energy (BE) in the Mediterranean region, with focus on the region around Cyprus. Previous studies are reviewed, the main findings of the blue energy potential analysis performed in the frame of the MAESTRALE project are presented, and the most promising blue energy sources for the Mediterranean are highlighted. The findings of this report suggest that there is a good exploitability potential of different forms of BE in the Mediterranean. The most highlig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 16 publications
0
6
0
Order By: Relevance
“…( 4). There are two important components that determine the value of wave energy [41]. These are the wave height and the wave period value.…”
Section: Wave Energy Potentialmentioning
confidence: 99%
“…( 4). There are two important components that determine the value of wave energy [41]. These are the wave height and the wave period value.…”
Section: Wave Energy Potentialmentioning
confidence: 99%
“…According to European Commission communications on Blue Energy (EC, 2012;EC, 2014), offshore wind and marine technologies can generate electricity and contribute towards sustainable development. In fact, technological developments can positively impact the supply of sustainable electricity, even though average potentials in the Mediterranean Sea are lower than those found in the North Sea and the oceans (Golfetti et al, 2018;Nikolaidis et al, 2019). Research into the exploitation of marine energy has produced significant advances which have the potential to expedite the process of ecological transition (Pisacane et al, 2018) but there are still issues that need to be explored (Golfetti et al, 2018).…”
Section: Seascape and Blue Energymentioning
confidence: 99%
“…A recent assessment of the energy potential in the Mediterranean Sea, with focus on coastal areas, has been given by Nikolaidis et al (2019), who presented results of the Interreg MED project Maestrale (https://maestrale.interregmed.eu). It was found that the most promising fonts are the offshore wind energy and the wave energy, which can be extracted both offshore, using floating devices (see, e.g., Pisacane et al, 2018, and references therein), and on shore, with devices embedded in ports or wave-breakers (e. g., Barbarelli et al, 2018).…”
Section: Introductionmentioning
confidence: 99%